In vitro ANTIGIARDIAL ACTIVITY OF THE CYSTEINE PROTEASE INHIBITOR E-64 - Carvalho, Thais Batista de; Oliveira-Sequeira, Teresa Cristina Goulart; Guimaraes, Semiramis (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The quest for new antiparasitic alternatives has led researchers to base their studies on insights into biology, host-parasite interactions and pathogenesis. In this context, proteases and their inhibitors are focused, respectively, as druggable targets and new therapy alternatives. Herein, we proposed to evaluate the in vitro effect of the cysteine protease inhibitor E-64 on Giardia trophozoites growth, adherence and viability. Trophozoites (105) were exposed to E-64 at different final concentrations, for 24, 48 and 72 h at 37 °C. In the growth and adherence assays, the number of trophozoites was estimated microscopically in a haemocytometer, whereas cell viability was evaluated by a dye-reduction assay using MTT. The E-64 inhibitor showed effect on growth, adherence and viability of trophozoites, however, its better performance was detected in the 100 µM-treated cultures. Although metronidazole was more effective, the E-64 was shown to be able to inhibit growth, adherence and viability rates by ≥ 50%. These results reveal that E-64 can interfere in some crucial processes to the parasite survival and they open perspectives for future investigations in order to confirm the real antigiardial potential of the protease inhibitors.